Cutaneous Manifestations of Cancers of the Gastrointestinal Tract: a Narrative Literature Review - Pałdyna, Marianna; Rogalska, Weronika; Baran, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2025)
Cancers of the gastrointestinal tract represent a significant public health concern. Due to the increasing prevalence of these conditions, promoting knowledge about cancer-associated manifestations is crucial. Among these are skin manifestations, which can present a range of clinical features, from small melanotic macules on the lips to multiple epidermal cysts or desmoid tumors. Early detection of skin manifestations can significantly improve the prognosis and provide more effective treatment options for patients. The key to diagnosing cancer lies in a thorough examination of the entire skin by an experienced physician. The aim of this review is to summarize the skin manifestations of gastrointestinal tract cancers, thus facilitating further diagnosis for patients presenting with symptoms associated with progressing carcinogenesis.